UPAYA MENINGKATKAN EFEKTIVITAS BELAJAR PENDIDIKAN JASMANI OLAH RAGA DAN KESEHATAN TENTANG LEMPAR TURBO DENGAN MEDIA BOLA KASTI KELAS VI SD NEGERI WAIWERAMG KABUPATEN FLORES TIMUR TAHUN 2016/2017 - Martinus Aran Baka (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2018)
In the back of this research, the implementation of the Physical and Health Physical Education Study Program in Waiwerang Elementary School was running smoothly because it was not supported by adequate sports facilities or equipment. For this one thing the creation of physical education teachers is needed to be able to find a solution to overcome this gap so that the learning material that becomes the demand of the curriculum can be implemented well, even though it is far from the actual expectations. The research method used is action research. Whereas the population and sample in this study were the sixth grade population of SD Negeri Waiwerang in East Adonara District, East Flores Regency in the 2016/2017 academic year which numbered 27 people. The procedures of the research conducted included: Planning, Implementation, Observation and reflection. Through the drill learning approach and playing tubro throwing using ball media, motivated students to move actively in learning. This is evident from the results of the analysis of cycle one to cycle two experienced an increase in terms of: activity, sincerity, discipline and throwing performance through a measuring instrument. In the pre-cycle of 27 children there were only 18 children who received grades 7 to 8. Or kl = 48.60%. While the remaining 9 children get a score of 6 to take. Or the range of 33.33%. After the implementation of the first cycle it turns out that the student's score has increased, namely 25 children got a score of 7 and above or a range of 92.59%. The remaining 2 other students get a value of 6. From this data, there is a significant increase in turbo learning using ball media